Analisis Kadar Monosodium Glutamat (MSG) pada Bumbu Mie Instan yang Diperjualbelikan di Koperasi Wisata Universitas Indonesia Timur - Sri Sulastri (Jurnal Media Laboran, 2017)
Monosodium glutamate (MSG) is a sodium salt of glutamic acid (a non-essential amino acid). Monosodium glutamate is widely used as a flavoring in foods. This study aims to determine the levels of monosodium glutamate on instant noodle spice traded in Tourism Cooperative University of East Indonesia. The type of this research was conducted by laboratory experiments with sampling technique using purposive sampling using 5 samples of instant noodle spice and examination method that is titration method. Based on the results of research that has been done then the monosodium glutamate content of the 5 samples are 14.5%, 16%, 16.5%, 18.8% and 21.5% where the lowest MSG levels are found in sample D with levels of 14, 5% and the highest level on sample E with content of 21,5% with weight of MSG from 5 sample is 0.016 gr, 0.0188 gr, 0.0162 gr, 0.0145 gr and 0.0215 gr. Therefore, instant noodles can be consumed 1 pack per day viewed from the weight of MSG which is still below the established threshold of 0.3-1 gr per day.